The impact of eggshell colour and spot area in Japanese quails: I. eggshell temperature during incubation and hatching results - Sema Alasahan; Gulsen Copur Akpinar; Sibel Canogullari; Mikail Baylan (Revista Brasileira de Zootecnia, 2016)
ABSTRACT This study was carried out to investigate the effects of eggshell colour and spot properties (colour and size of the spot area) on eggshell incubation temperature and hatching outcomes of Japanese quail eggs (Coturnix coturnix japonica). Study material was allocated to five groups according to their eggshell and spot colours: black spots on greyish white coloured eggshell (I), blue spots on greyish white coloured eggshell (II), diffuse brown spots on greyish brown coloured eggshell (III), brown spots on light green coloured eggshell (IV), and small brown spots on greyish brown coloured eggshell (V). The size of the spotted area was determined in each egg group using digital image analysis. Mean relative weight losses of hatched and unhatched eggs between days 0-10 and 0-14 of embryonic development were 4.76% and 10.48% and 9.17% and 15.46%, respectively. The mean eggshell temperatures of hatched and unhatched eggs measured at the equatorial region on days 10 and 14 during embryonic development were 36.92 and 37.79 ºC and 36.84 and 37.18 ºC, respectively. Eggshell temperatures at the equatorial region on days 10 (36.89 ºC) and 14 (37.57 ºC) of embryonic development were lower than the fixed temperature of the incubator (37.6 ºC). Fertility, hatchability of fertile eggs, and hatchability and embryonic mortality rates do not vary in relation to eggshell colour or the size of the spotted area.